Role of Teachers in the Implementation of Students’ Code of Conduct in Economics Learning Process - Yulia Novita; Salmia Salmia; Dicki Hartanto; Novian Aldo; Alfiah Alfiah (AL-ISHLAH: Jurnal Pendidikan, 2022)
This research was designed to know the implementation of student code of conduct in the Economics learning process. The subjects of this research were the Economics subject teachers, and the object was the implementation of student code of conduct in the Economics learning process at Social Science Department of Senior High School of Muhammadiyah 1 Pekanbaru.  The informants of this research were two Economic teachers.  The techniques of collecting the data were direct observation, interview notes and recording the respondent answer and documentation.  The technique of analyzing the data was descriptive qualitative. Based on the data presentation and analysis, it could be concluded that the role of teachers in the implementation of student code of conduct in the Economics learning process at Social Science Department of Senior High School was  in the percentage of 73,43% in the range of 61%-80% and included in good category